Functional and evolutionary analyses of Helicobacter pylori HP0231 (DsbK) protein with strong oxidative and chaperone activity characterized by a highly diverged dimerization domain - Bocian-Ostrzycka, Katarzyna M.; Łasica, Anna M.; Dunin-Horkawicz, Stanisław; Grzeszczuk, Magdalena J.; Drabik, Karolina; Dobosz, Aneta M.; Godlewska, Renata; Nowak, Elżbieta; Collet, Jean-Francois; Jagusztyn-Krynicka, Elżbieta K. (Frontiers in Microbiology, 2015)
Helicobacter pylori does not encode the classical DsbA/DsbB oxidoreductases that are crucial for oxidative folding of extracytoplasmic proteins. Instead, this microorganism encodes an untypical two proteins playing a role in disulfide bond formation – periplasmic HP0231, which structure resembles that of EcDsbC/DsbG, and its redox partner, a membrane protein HpDsbI (HP0595) with a -propeller structure. The aim of presented work was to assess relations between HP0231 structure and function. We showed that HP0231 is most closely related evolutionarily to the catalytic domain of DsbG, even though it possesses a catalytic motif typical for canonical DsbA proteins. Similarly, the highly diverged N-terminal dimerization domain is homologous to the dimerization domain of DsbG. To better understand the functioning of this atypical oxidoreductase, we examined its activity using in vivo and in vitro experiments. We found that HP0231 exhibits oxidizing and chaperone activities but no isomerizing activity, even though H. pylori does not contain a classical DsbC. We also show that HP0231 is not involved in the introduction of disulfide bonds into HcpC (Helicobacter cysteine-rich protein C), a protein involved in the modulation of the H. pylori interaction with its host. Additionally, we also constructed a truncated version of HP0231 lacking the dimerization domain, denoted HP0231m, and showed that it acts in E. coli cells in a DsbB-dependent manner. In contrast, HP0231m and classical monomeric EcDsbA (Escherichia coli DsbA protein) were both unable to complement the lack of HP0231 in H. pylori cells, though they exist in oxidized forms. HP0231m is inactive in the insulin reduction assay and possesses high chaperone activity, in contrast to EcDsbA. In conclusion, HP0231 combines oxidative functions characteristic of DsbA proteins and chaperone activity characteristic of DsbC/DsbG, and it lacks isomerization activity.